Automatic transfer of chips from tray to tube - Chen, Qi Ming. (2008)
The report reviewed the developing background of the automation equipment in semiconductor industry; and how to achieve a high efficient and qualitative work by building a high technology automatic machine. The dissertation presents design concepts in design procedures and analysis of the problems encountered, as well as how to achieve a better effect of user interface.